Dental management of bilirubin encephalopathy patient: A case report and review - Poornima Parameswarappa; Rupali Sharma; Roopa Korishettar; Neena Eregowda (Wolters Kluwer Medknow Publications, 2017)
Patients with special health care needs often present with compromised oral health for which they need dental treatment. Such patients and often their guardians find it difficult to maintain oral health due to various reasons such as decreased manual dexterity and preference for soft diet. Bilirubin encephalopathy is a condition occurring as a result of neonatal jaundice/hyperbilirubinemia. Elevated levels of unconjugated bilirubin at birth often leads to brain damage manifesting as auditory and motor defects such as athetoid cerebral palsy. This paper reports one such case of dental management of a known case of bilirubin encephalopathy.